DOP36 Non-invasive assessment of postoperative disease recurrence in Crohn's Disease: A multicenter, prospective cohort study. (27th May 2021) - Furfaro, F; Zilli, A; Craviotto, V; Aratari, A; Bezzio, C; Gilardi, D; D'Amico, F; Saibeni, S; Papi, C; Peyrin-Biroulet, L; Fiorino, G; Danese, S; et al.
Abstract: Background: Prevention of postoperative recurrence is a critical goal in Crohn's disease (CD) management. Currently, postsurgical CD management and treatment are based on endoscopic monitoring performed within the first year after surgery. However, colonoscopy (CS) is an invasive and expensive procedure, unpleasant to patients. A non-invasive and patient friendly approach is required. Methods: Consecutive CD patients who underwent ileo-cecal resection from July 2017 to January 2020 were prospectively enrolled in three Italian Centers and performed CS and bowel ultrasound (US) after six months from the surgery, in a blinded fashion. The patients also underwent complete clinical assessment and blood and stool samples were obtained for C-reactive protein (CRP), and fecal calprotectin (FC) measurements. The disease was considered clinically active if the Harvey–Bradshaw Index (HBI) was higher than 4. Uni- and multivariable analyses were used to assess the correlation between non-invasive parameters, including bowel US findings and FC values and endoscopic recurrence, defined by a Rutgeerts's score (RS) > 2. Sensitivity, specificity, accuracy, PPV and NPV of bowel US parameters alone and in combination with FC in assessing endoscopic recurrence were calculated. Results: Seventy patients were enrolled, 45 patients (64%) had an endoscopic recurrence (RS > 2) at 6 months. Thirteen out of 45 (29%) were symptomatic (HBI > 4). Bowel wall thickness (BWT), bowel wall flow (BWF, presence of vascular signals at color Doppler), the presence of mesenteric hypertrophy, the presence of limph-nodes and FC values significantly correlated with the endoscopic recurrence (p < 0.005). Independent predictors for endoscopic recurrence were BWT (for 1-mm increase: OR 2.63; 95% CI 1.136.12; p= 0.024), presence of lymph-nodes (OR 23.24; 95% CI 1.85291.15; p= 0.014) and FC > 50 µg/g (OR 11.86; 95% CI 2.60–54.09; p= 0.001). Sensitivity, specificity, accuracy, PPV and NPV of bowel US and/or FC are showed in Table 1. Table 1: Diagnostic accuracy of Bowel US and/or FC compared to CS in assessing endoscopic activity (CI 95%): per-patient analysis Conclusion: Combined use of bowel US and FC is accurate in assessing endoscopic recurrence at 6 months in CD patients and represent a valid alternative to endoscopic assessment after surgery